Nutrient content in Malaysia torch ginger flower (Etlingera elatior) - Nazikussabah, Zaharudin; Hazrulrizawati, Hamid; Dzulkaflee, N. F. (2017)
Torch ginger flower (Etlingera elatior) is a wild and edible flower that can found in the rainforest of Malaysia. It is use in cooking as seasoning of nutrition additive and crucial elements in some traditional foods of Malaysia. In this study, nutrient content of Etlingera elatior was determined. The proximate composition protein, fat, dietary fiber, carbohydrate, ash and energy, moisture and vitamin were studied. The results suggest that Etlingera elatior has high content of fiber, fat and protein. Etlingera elatior are also containing wide range of constituents such as vitamins. Perhaps these nutritional characteristics can be used as information for the human food and their potential in the food and nutraceutical industries.